Faktor - Faktor Yang Berhubungan Dengan Motivasi Perawat Melanjutkan Pendidikan Tinggi Keperawatan Di Rumah Sakit Islam Surakarta - Supriyanti, Supriyanti; , Abi Muhlisin, SKM, M.Kep; , Endang Zulaicha S usilaningsih , S.Kp ., M.Kep (2015)
Development of nursing education to reach a professional nursing's global purpose and educated, must have motivation in fostering knowledge and skill that possessed of. Motivation is an action that carry out by human, and begin with intention or some internal or external process for an individual that cause attitude, enthusiastic, and persistent in carry out certain activity. Endorser system and appreciation to nurses will bring good effect for nurse's performance, beside that work environment can prioritized intellectual development and personality that can be carry out by education. The purpose of this study was to know factors related to nurse's motivation continuing advanced nursing education in Islamic Hospital of Surakarta. This study was a descriptive quantitative. Total population in this study 297 nurses, with 75 nurses used as respondents which used proporsional random sampling method. Instrument of this study is a questions. Variable that used in this study are organization policy, age, salary, and position as independent variable, and motivation as dependent variable. Chi-square test were used as data analysis technique, with level of significance α = 0,05. The results of this study showed that organization policy significance value χ2-arithmetic (1,339) < χ2 table (3,841) and age significance value χ2-arithmetic (1,422) < Table χ2 (5,991), H0 accepted. Whereas position significance value χ2-arithmetic (4.837) > Table χ2 (3.841) and salary significance value also χ2-arithmetic (5.013) > Table χ2 (3.841), H0 rejected. This study shows that there is significance connection between salary and position with nurse's motivation to continuing education and not have significance connection between organization policy and age with nurse's motivation to continuing advanced nursing education in Islamic Hospital of Surakarta.